Earthquake Engineering in Europe - Garevski, Mihail; Ansal, Atilla; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This book contains 9 invited keynote and 12 theme lectures presented at the 14th European Conference on Earthquake Engineering (14ECEE) held in Ohrid, Republic of Macedonia, from August 30 to September 3, 2010. The conference was organized by the Macedonian Association for Earthquake Engineering (MAEE), under the auspices of European Association for Earthquake Engineering (EAEE). The book is organized in twenty one state-of-the-art papers written by carefully selected very eminent researchers mainly from Europe but also from USA and Japan. The contributions provide a very comprehensive collection of topics on earthquake engineering, as well as interdisciplinary subjects such as engineering seismology and seismic risk assessment and management. Engineering seismology, geotechnical earthquake engineering, seismic performance of buildings, earthquake resistant engineering structures, new techniques and technologies and managing risk in seismic regions are all among the different topics covered in this book. The book also includes the First Ambraseys Distinguished Award Lecture given by Prof. Theo P. Tassios in the honor of Prof. Nicholas N. Ambraseys. The aim is to present the current state of knowledge and engineering practice, addressing recent and ongoing developments while also projecting innovative ideas for future research and development. It is not always possible to have so many selected manuscripts within the broad spectrum of earthquake engineering thus the book is unique in one sense and may serve as a good reference book for researchers in this field. Audience: This book will be of interest to civil engineers in the fields of geotechnical and structural earthquake engineering; scientists and researchers in the fields of seismology, geology and geophysics. Not only scientists, engineers and students, but also those interested in earthquake hazard assessment and mitigation will find in this book the most recent advances.
Engineering Seismology -- Seismic Engineering of Monuments -- Microzonation for Earthquake Scenarios -- Analysis of Regional Ground Motion Variations for Engineering Application -- Geotechnical Earthquake Engineering -- Non Linear Soil Structure Interaction: Impact on the Seismic Response of Structures -- From Non-invasive Site Characterization to Site Amplification: Recent Advances in the Use of Ambient Vibration Measurements -- Effects of Non-plastic Fines on Liquefaction Resistance of Sandy Soils -- Seismic Performance of Buildings -- Performance Based Seismic Design of Tall Buildings -- Evaluation of Analysis Procedures for Seismic Assessment and Retrofit Design -- Reflections on the Rehabilitation and the Retrofit of Historical Constructions -- Engineers Understanding of Earthquakes Demand and Structures Response -- Current Trends in the Seismic Design and Assessment of Buildings -- Performance-Based Design of Tall Reinforced Concrete Core Wall Buildings -- Earthquake Resistant Engineering Structures -- Open Issues in the Seismic Design and Assessment of Bridges -- Recent Developments on Structural Health Monitoring and Data Analyses -- New Techniques and Technologies -- Large Scale Testing -- The Contribution of Shaking Tables to Early Developments in Earthquake Engineering -- Development, Production and Implementation of Low Cost Rubber Bearings -- Managing Risk In Seismic Regions -- Investing Today for a Safer Future: How the Hyogo Framework for Action can Contribute to Reducing Deaths During Earthquakes -- Emergency and Post-emergency Management of the Abruzzi Earthquake -- L$1 (BAquila 6th April 2009 Earthquake: Emergency and Post-emergency Activities on Cultural Heritage Buildings -- Rapid Earthquake Loss Assessment After Damaging Earthquakes -- Catastrophe Micro-Insurance for Those at the Bottom of the Pyramid: Bridging the Last Mile.s
Keywords: Geography; Engineering; Civil engineering; Hydraulic engineering; Soil conservation; Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Civil Engineering; Geoengineering, Foundations, Hydraulics; Soil Science & Conservation; Computational Intelligence